Psychometric Validating a Video-Based Rubric for Physics Teacher Assessment Using the Rasch Model - Kusumaningtyas, Dian Artha; Bakri, Yuhanis Mhd; Adhantoro, Muhammad Syahriandi; Ishafit, Ishafit; Kurniasari, Efi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to validate the psychometric properties of a video-based assessment rubric designed to evaluate the pedagogical and professional competencies of physics prospective teachers. The validation process employed the Rasch model to examine item reliability, person reliability, item fit, category functioning, and the separation index. Data were collected from 61 participants using a 25-item rubric that covered various aspects, including Pancasila values, instructional structure, student-centered learning, professional ethics, and evaluation of learning. The results showed that the item reliability was high (0.83), while person reliability was moderate (0.75), with a person separation index of 1.75. Some items exhibited misfit with the Rasch model, indicating the need for revision or refinement. Analysis of category functioning revealed overlapping probabilities between adjacent categories, suggesting that the response scale could benefit from more precise distinctions. Overall, the rubric demonstrated acceptable psychometric quality for assessing the competencies of physics prospective teachers, although several items and scale structures require improvement to enhance measurement precision